The Impact Of Transformational Leadership Style On Employee Performance And Organizational Innovation In Five-star Hotels In The Kingdom Of Saudi Arabia - Mohammad Helalat, Abdullah Saleh (2019)
The rapid changes and the growth of the global environment, as well as the high competition amongst hospitality industry companies to obtain competitive benefits require well-prepared leadership qualities, commitment to employees, and concerted efforts for innovative approaches. In this study, the transformational leadership style is tested by four components; the employee performance is tested by two components, and the organizational innovation is tested by product innovation and process. This study investigates the impact of the transformational leadership style on the employee performance and organizational innovation in the Saudi hotel industry context. However, research on the Saudi hotel industry is scarce. To address this gap, this study contributes to the existing research on the hospitality industry, as well as to the hoteliers. The Saudi hotel industry and its success is very important to be investigated as a case study. Seventy-two local and international five-star hotels in Makkah and Madinah have been chosen. Rank-and-file employees are the respondents of this study, which includes a sample of 371 respondents. A quantitative research method is used to obtain the results, and Google link containing the survey form is administered to the selected hotels. Data were statistically analysed using SMART-PLS. The study found 36 hypotheses based on the relationships between the studied variables, whereby 16 hypotheses from a total of 36 were found to be positive, and 20 hypotheses were rejected